KONFLIK PEMIKIRAN METODE ISTINBATH HUKUM MADZHAB HANAFIYYAH DAN SYAFI’IYYAH DALAM HUKUM NIKAH TANPA WALI - Muhammad, Yasfin Maulana; Israqunnajah, Israqunnajah; Fakhruddin, Fakhruddin; Rahmani, Mufti (JURNAL AL-IJTIMAIYYAH, 2022)
Abstract: The role of the guardian in marriage in Islamic family law is an important requirement with the presence of a guardian in the marriage. Basically, the presence of a guardian in a marriage or contract intends to maintain and protect the rights of a woman. Discussions about guardians in marriage, scholars differ in their opinion, including on the role of a guardian in marriage. The guardian has the full right to guardianship (prospective bride) in marriage, including as the utterance of the Ijab sentence to the prospective groom. A guardian in a marriage has a position. The Syafiiyyah Madhhab said that the role of a guardian in a marriage is a condition for the validity of a marriage contract. This is different from the opinion of the Hanafiyyah School which says that marriage is considered valid even though there is no female guardian. From this explanation, there are differences of opinion between Hanafiyyah and Syafi'iyyah in the law of tabpa wali marriage. (1) The Hanafiyyah School concludes that the marriage of a woman (a virgin or a widow) is considered valid even though she does not use a guardian in her marriage and the pillars of marriage according to the Hanafiyyah scholars are only consent and qabul. (2) The Syafii'iyyah school concludes that any woman who wants to get married is obliged to present her guardian and two just men as witnesses and the pillars of marriage according to the Syafi'iyyah scholars are consent and qabul, both the bride and the guardian.Keywords: Thought; Legal Istinbath Method; Madhab; Marriage without Guardian.Abstrak: Peran wali dalam perkawinan dalam hukum keluarga Islam merupakan syarat penting dengan hadirnya seorang wali dalam perkawinan. Pada dasarnya hadirnya seorang wali dalam perkawinan atau akad bermaksud untuk menjaga dan melindungi atas hak seorang perempuan tersebut. Pembahasan seputar wali dalam pernikahan para ulama berbeda-beda dalam berpendapat diantaranya pada peran seorang wali dalam pernikahan. Wali berhak penuh atas pewalian (calon mempelai perempuan) dalam perkawinan diantaranya sebagai pengucap kalimat ijab terhadap calon pengantin laki-laki. Seorang wali dalam sebuah pernikahan mempunyai kedudukan. Madzhab Syafiiyyah mengatakan peran seorang wali dalam sebuah pernikahan adalah sebagai syarat sah nya sebuah akad pernikahan. Berbeda dengan pendapat madzhab Hanafiyyah yang mengatakan pernikahan dianggap sah walaupun tidak adanya wali dari pihak perempuan. Dari pemaparan tersebut terdapat adanya perbedaan pendapat anatara hanafiyyah dan Syafi’iyyah dalam hukum nikah tabpa wali. (1) Madzhab Hanafiyyah menyimpulkan pernikahan perempuan (perawan atau janda) dianggap sah walaupun tidak menggunakan wali dalam pernikanya dan rukun nikah menurut para ulama Hanafiyyah hanya ijab dan qabul. (2) Madzhab Syafii’iyyah menyimpulan bahwa seorang perempuan mana pun yang hendak ingin menikah maka wajib menghadirkan walinya dan dua orang lelaki yang adil sebagai saksi dan rukun nikah menurut para ulama Syafi’iyyah adalah ijab dan qabul, kedua mempelai dan wali.Kata Kunci: Pemikiran; Metode Istinbath Hukum; Madzhab; Nikah Tanpa Wali.